Influence of Air Gap Distribution in E-type Cores - Herrero Gracia, Lucas; Pérez Cebolla, Francisco José; Puyal Ventura, Álex; Bernal Ruiz, Carlos (Jornada de Jóvenes Investigadores del I3A, 2025)
This work analyzes the magnetic behavior of E-type cores by modifying the air gap configuration. Three different arrangements are compared, and their impact on flux distribution and losses is evaluated to improve design efficiency.